2017
DOI: 10.1007/s11239-017-1543-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common hereditary risk factors for thrombophilia in Somalia and identification of a novel Gln544Arg mutation in coagulation factor V

Abstract: Thrombophilia, commonly manifested as venous thromboembolism (VTE), is a worldwide concern but little is known on its genetic epidemiology in many parts of the globe particularly in the developing countries. Here we employed TaqMan genotyping and pyrosequencing to evaluate the prevalence of known common nucleotide polymorphisms associated with thrombophilia in a Somali population in the Puntland region of Somalia. We also employed next generation sequencing (NGS) to investigate other genetic variants in a Soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The proportion of Rh+ and Rh-were 88% and 12%, respectively. These results were consistent with the previously reported Somali phenotype blood group data 26 as well as with our previous O blood group genotype assessments for ethnic Somalis 27 . We also examined the distribution of Apolipoprotein E (ApoE) gene variants in the Somali population using the SNPs rs429358 and rs7412.…”
Section: Genotype Data Verificationsupporting
confidence: 93%
“…The proportion of Rh+ and Rh-were 88% and 12%, respectively. These results were consistent with the previously reported Somali phenotype blood group data 26 as well as with our previous O blood group genotype assessments for ethnic Somalis 27 . We also examined the distribution of Apolipoprotein E (ApoE) gene variants in the Somali population using the SNPs rs429358 and rs7412.…”
Section: Genotype Data Verificationsupporting
confidence: 93%
“…A study conducted in Somalia showed that these common genetic risk factors, most known for VTE, are absent or less frequent in this group, when compared to other ethnic populations. 35 Our population had very few individuals of Afro-descendant origin (3%), which could explain the higher prevalence of these variants. However, this study was limited by its sample size.…”
Section: Discussionmentioning
confidence: 84%
“…One of these, rs61742245 (VKORC1 Asp36Tyr), was prevalent only in the SOM population. This variant is included in the 8% ‘C G C C G G A A’ haplotype in Table 1 , as mentioned above, and is associated with warfarin resistance in the Horn of Africa [ 19 21 ] and, to a lesser extent, in the Middle East [ 22 , 23 ]. The two genetically most distinct populations from Europe (YRI and EAS) had also the fewest number of drug response variants that reached the threshold of 1% AAF.…”
Section: Resultsmentioning
confidence: 99%